Immunity to error through misidentification : new essays - Prosser, Simon; Récanati, François, 1952- (Cambridge University Press, 2012)
"Immunity to error through misidentification is recognised as an important feature of certain kinds of first-person judgments, as well as arguably being a feature of other indexical or demonstrative judgments. In this collection of newly commissioned essays, the contributors present a variety of approaches to it, engaging with historical and empirical aspects of the subject as well as contemporary philosophical work. It is the first collection of essays devoted exclusively to the topic and will be essential reading for anyone interested in philosophical work on the self, first-person thought or indexical thought more generally"--